Pengaruh Literasi Keuangan Digital, Kepercayaan Konsumen dan Perilaku Risiko Keuangan terhadap Minat Bertransaksi Menggunakan QRIS di Era Digital: Studi Kasus pada Konsumen di Sarimulya Swalayan, Brebes - Yuniarti Ma’nawiyah; Dwi Harini; Hendri Sucipto; Azizah Indriyani; Slamet Bambang Riono (Pusat Riset dan Inovasi Nasional, 2025)
Although the Quick Response Code Indonesian Standard (QRIS) has been widely adopted across various retail sectors, its utilization at the local level remains suboptimal, as evidenced in Sarimulya Swalayan Brebes. This study aims to analyze the influence of digital financial literacy, consumer trust, and financial risk behavior on consumers’ interest in conducting transactions using QRIS in the digital era. The research employed a quantitative method with a survey approach involving 139 respondents who were customers of Sarimulya Swalayan. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression with the assistance of statistical software. The findings reveal that digital financial literacy, consumer trust, and financial risk behavior each have a significant partial influence on the intention to transact using QRIS, while simultaneously, these three independent variables also significantly affect the dependent variable. The results emphasize that improving digital financial literacy helps consumers better understand the operational mechanisms, benefits, and security aspects of QRIS transactions, thereby reducing uncertainty and hesitation in its usage. Moreover, consumer trust in the system is confirmed as a key determinant in fostering willingness to adopt QRIS, as confidence in the reliability and safety of the service encourages greater acceptance of digital payments. In addition, financial risk behavior plays an essential role in guiding consumers to remain prudent, careful, and rational when utilizing QRIS-based payment services. Overall, this study highlights the importance of strengthening digital financial education, enhancing consumer trust, and managing financial risks as strategic measures to support the adoption and sustainability of QRIS, particularly in the context of local retail.